Frequency of Restless Leg Syndrome in Diabetic Patients and it’s Impact on Quality of Life - Abdul Manan, Zubair Ahmad, Wasfa Aijaz, Muhammad Kamran, Fayaz Ahmed Memon, Faizan Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to assess the prevalence of RLS and its effect on quality of life in diabetic patients. Study Design: Cross-sectional/Comparative study Place and Duration: Department of Medicine, Hayatabad Medical Complex, Peshawar in the duration from June, 2022 to November, 2022. Methods: There were 114 diabetic and non diabetic patients were presented in this study. After obtaining informed written consent detailed demographics of enrolled cases were recorded. Patients were distributed in two groups, group I had 57 diabetic patients and groups II had 57 diabetic patients. Both groups were diagnosed with RLS using the International RLS Study Group’s diagnostic criteria. SPSS 23.0 was used to analyze all data. Results: There were majority females 30 (52.6%) in group I and 33 (57.9%) in group II. Mean age of the patients in group I was 49.17±9.48 years and in group II mean age was 46.12±11.85 years. Frequency of HTN in group I was found in 22 (38.6%) cases and in group II its frequency was 13 (22.8%). RLS in group I was found in 19 (33.3%) cases and in group II found in 5 (8.8%) cases. Frequency of retinopathy, neuropathy and abnormal neck circumference was significantly higher in diabetic cases as compared to non-diabetic with p value <0.002. Conclusion: This study’s findings suggest a strong link between RLS and diabetes, as well as a negative impact on the quality of life, health outcomes, sleep, daytime activity, cognitive function, and mental health of diabetic patients. Additionally, they suggest that doctors and other healthcare professionals should be more aware of RLS. Keywords: RLS, Diabetes, Retinopathy, Neuropathy, Quality of life